2020
DOI: 10.24269/hsj.v4i1.409
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Balita 1-5 Tahun

Abstract: Pemberia ASI eksklusif pada bayi 0-6 bulan dengan cara yang benar sangat penting untuk mencegah terjadinya gizi buruk, atau lebih parah lagi dalam jangka panjang tanpa penanganan yang tepat dapat menyebabkan Stunting . Stunting  menyebabkan tingkat kecerdasan yang kurang, rentan terhadap penyakit, dimasa depan menurunkan tingkat produktivitas, secara luas dapat menghambat pertumbuhan ekonomi dan meningkatkan kemiskinan. Tujuan Penelitian ini yaitu untuk mengetahui hubungan pemberian ASI eksklusif dengan kejadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 0 publications
3
7
0
21
Order By: Relevance
“…The study in Jaya Bakti Village shows that children below 60 months that are not receiving exclusive breastfeeding and have a risk of developing stunting are 28 (93.3%) compared to toddlers that received it. These results are in line with a study conducted by Badriyah and Syafiq [3], Lestari et al [8], and Latifah et al [9] which stated that the incidence of stunting is influenced by exclusive breastfeeding because breast milk contains antibodies that increase the baby's immune system. Therefore, the baby is prevented from sickness such as diarrhea, while malnutrition disturbed and posed the baby at risk which affects growth and causes stunting.…”
Section: Discussionsupporting
confidence: 90%
“…The study in Jaya Bakti Village shows that children below 60 months that are not receiving exclusive breastfeeding and have a risk of developing stunting are 28 (93.3%) compared to toddlers that received it. These results are in line with a study conducted by Badriyah and Syafiq [3], Lestari et al [8], and Latifah et al [9] which stated that the incidence of stunting is influenced by exclusive breastfeeding because breast milk contains antibodies that increase the baby's immune system. Therefore, the baby is prevented from sickness such as diarrhea, while malnutrition disturbed and posed the baby at risk which affects growth and causes stunting.…”
Section: Discussionsupporting
confidence: 90%
“…Pemberian ASI ekslusif diketahui dapat mencegah terjadinya stunting pada anak (Sampe, Toban, & Madi, 2020). Bayi baru lahir perlu mendapat perawatan yang optimal sejak dini, termasuk pemberian makanan yang ideal.…”
Section: Pendahuluanunclassified
“…Among the features of breast milk, it is also mentioned that breast milk contains high levels of calcium and antibodies and is easily absorbed by the baby's body so that the baby's bone formation can be optimal. Under these conditions, of course, it can be concluded that exclusive breastfeeding can reduce the risk of stunting (Latifah et al, 2020). Central Sulawesi Province ranks tenth for the proportion of stunting (TB/U) with a stunting rate of 31.26% in children under five.…”
Section: Introductionmentioning
confidence: 99%